Etos wodza w twórczości Samuela Twardowskiego - Kuran, Michał (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2005)
In this paper the author shows a few personifications the commander in Samuel Twardowski’s heroic creation. He chooses only theses situations, which the poet presents his principal hero only in the very important situation for the republic’s history. The author showed headman election, hetmans death, why he acts as the hetman to his death, the commander as orator, the hetman as negotiator and the commander on the battlefield. The author described few important military situations, in the knight’s live seventeenth century commanders, for instance: Stanisław Żółkiewski, Jan Karol Chodkiewicz, Jeremi Wiśniowiecki etc., when they spoke to his knight, when they fought and sometimes died. In the commanders’ ethos was of importance, in the Twardowski’s creation and in all old Polish culture, that he combined elements of senator, diplomat, orator, headman and knights.